THE INJUSTICE OF EARLY MARRIAGE ON THE DEVELOPMENT OF THE GIRL CHILD IN DELTA STATE, NIGERIA - Benedict AKPOMUVIE, Orhioghene; OKINONO, Otega (International Journal of Psychosocial Rehabilitation, 2020)
The article critically examined the socio-economic effects of early marriage on the girl-child in Nigeria, using Delta State as a case study with which to generalize on the country because of similarities in the practice. Early marriage is not new among many ethnic groups of the world particularly in Nigeria. However, the practice is the product of tradition, culture and religion. The study which utilized the in-depth and key informant interviews and group focus discussions revealed that child marriage is a common feature in the communities studied with its attendant negative reverberations on the girl-child and society. It further showed that it may likely not discontinue despite conventions against it. The study however recommended intervention strategies to equip the girls in all ramifications to free them from the burden of forced marriages and guarantee their future wellbeing.